Serum Irisin Level Is Positively Associated with Bone Mineral Density in Patients on Maintenance Hemodialysis. (25th January 2021) - Lu, Chia-Wen; Wang, Chih-Hsien; Lin, Yu-Li; Kuo, Chiu-Huang; Lai, Yu-Hsien; Hsu, Bang-Gee; Tsai, Jen-Pi
Abstract : Background . Irisin is a circulating hormone-like myokine that plays an important role in bone metabolism. We performed a cross-sectional study to investigate whether serum irisin levels correlated with bone mineral density (BMD) in patients on maintenance hemodialysis (MHD). Methods . Blood samples were obtained from 80 patients on MHD, and serum irisin concentrations were determined using a commercially available enzyme-linked immunosorbent assay. BMD was measured by dual-energy X-ray absorptiometry of the L2–L4 vertebrae. Results . In the study cohort, 10 (12.5%) and 19 (23.8%) patients had osteoporosis and osteopenia, respectively, and 51 (63.75%) patients had normal BMD. Lumbar T-score was negatively associated with body height (P = 0.010 ), body weight (P = 0.002 ), body mass index (BMI, P = 0.010 ), and serum irisin (P < 0.001 ) and was positively associated with advanced age (P = 0.031 ), female sex (P = 0.001 ), alkaline phosphatase (ALP, P = 0.010 ), urea reduction rate (P = 0.018 ), and fractional clearance index for urea (P = 0.020 ). Multivariable forward stepwise linear regression analysis revealed that high serum logarithmically transformed irisin (log-irisin, β  = 0.450, adjusted R 2 change = 0.258; P < 0.001 ), female sex ( β  = −0.353, adjusted R 2 change = 0.134; P < 0.001 ), and serum ALP level ( β  = −0.176, adjusted R 2 change = 0.022; P = 0.049 ) were significantly and independently associated with lumbar BMD in patients on MHD. Conclusions . In addition to female sex and serum ALP level, serum irisin level was positively associated with lumbar BMD in patients on MHD.